2020
DOI: 10.31470/2309-1797-2020-27-1-164-180
|View full text |Cite
|
Sign up to set email alerts
|

Concept «Religion» in the Consciousness of Young People: Psycholinguistic Analysis

Abstract: Objective. The creation of the Orthodox Church of Ukraine is the reason of religious discourse investigation. The aim of this research is to analyze concept “religion” in the consciousness of young people. Materials & Methods. Free word association test (WAT) has been used for psycholinguistic analysis. The respondents have been received a questionnaire with ten words-stimuli (related to religious discourse: clergyman, priest, theologian, church, religion, preaching, sacraments, faith, sin, prayer). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Cognitive elaboration is linked to emotional and analytical thinking processing. Between 2020 and 2022, populations were immersed in negative states of mind (depression, loneliness and anxiety), which had a clear and direct effect on language development in adults and on language acquisition in children [7,8]. We found that the pandemic had negative effects on children's vocabulary and phonological awareness [9].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Cognitive elaboration is linked to emotional and analytical thinking processing. Between 2020 and 2022, populations were immersed in negative states of mind (depression, loneliness and anxiety), which had a clear and direct effect on language development in adults and on language acquisition in children [7,8]. We found that the pandemic had negative effects on children's vocabulary and phonological awareness [9].…”
Section: Introductionmentioning
confidence: 78%
“…Each individual's language usage therefore determines their psycholinguistic identity as well identifying their state of mind at a specific period. Discourses and corpora analyses make it possible to identify changes and biases in language communication, the development of lexicon and the evolution of semantics (meaning of things and referents) during and after the COVID-19 pandemic [7,8]. We should consider also the impact for the democratic environment, not only perceived as political setting, but changes in languages will have influence in the understanding of new forms of freedom (after lockdowns and restricted measures) and of engagement.…”
Section: Introductionmentioning
confidence: 99%
“…The character of God, his militancy, peace, the breadth of his interests, etc., largely determine the character of his subjects. If today the conversation about man can be conducted as if the heavens were empty, then the ancient man appears only in the company of his gods (Kostruba, 2020). Building relationships with the heavens, man determined his essence; since the forms of relations were different, the essence of man in different cultures was not identical.…”
Section: Statement Of Basic Materialsmentioning
confidence: 99%
“…I would like to emphasize that in the works that have appeared in recent years, the topic of moral consciousness of young people is studied in philosophical, ethical, environmental and sociological aspects (Melnik N. and others [1], Yan Wang and others [2]), Shepherd J. [3], Kostruba N. [4]; in the psychological aspect, the following works are interested: Linchenko A. [5], Manolov, M. [6], Revushkina M. B.…”
Section: Introductionmentioning
confidence: 99%